Family Rite of Khylbyk Doy of Urban Tuvans - Mainy, Shenne B. (The New Research of Tuva, 2021)
The article gives a full description of one of the Tuvan children’s rites — khylbyk doy (‘the rite of the first haircut’) which was held in 2018 in Kyzyl in honour of the third anniversary of a child. The ceremony was held as a festivity and brought together representatives of two kinship groups of the Tuvans — from the father’s side (kara-sal) and the mother’s side (khomushku). The features of this rite comprise holding in urban settings (tables were reserved in a café), innovations (in arranging and gifts) and borrowings from Western culture (cake-cutting in the end, a children’s show, etc.). The author shows the difference of the basic essence of the modern rite from the traditional one described in numerous ethnographic sources. In the past the rite symbolized the transition of a child from the age of an infant to childhood and acquiring their human rights, including the rights to be recognized by their relatives and to have personal property. The modern one can be rather considered as a joint event to maintain ethnic identity and kinship ties, to provide material support to the family and entertain children.